2010
DOI: 10.1002/ange.200906666
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Intramolecular Exchange Interaction in a Curved and Nonalternant π‐Conjugated System: Corannulene with Two Phenoxyl Radicals

Abstract: In recent years, curved p-conjugated molecules such as fullerenes and carbon nanotubes have attracted much attention not only in chemistry but also in materials science. [1] Their intra/intermolecular interactions within/between threedimensional (3D) curved p-electron networks play intrinsically vital roles in their unique properties and functionalities. Among them, intramolecular magnetic interaction between electronic spins on a curved p surface was extensively studied for ionic species of C 60 such as C 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The 1 H NMR spectra of cations 1-3 demonstrate the significantly high-field-shifted resonance signals for the CH x Cl 3Àx groups (0.12 ppm, 2.08 ppm, and 4.01 ppm for 1, 2, and 3, respectively) compared to those of CH 3 (Table 2). These values compare well with those found in the 13 C NMR spectra of C 70 -CHCl 2 + (198 ppm, in CF 3 SO 3 H) [6b] and in the protonated form of C 60 (182 ppm, 1,2-C 6 H 4 Cl 2 ). [12] The slight high-field shifts of the C3 resonances of the chlorinated cations 2-4 compared to that of 1 can most probably be attributed to the interaction of unshared electron pairs at the Cl atoms of the R groups with the cationic C3 center.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…The 1 H NMR spectra of cations 1-3 demonstrate the significantly high-field-shifted resonance signals for the CH x Cl 3Àx groups (0.12 ppm, 2.08 ppm, and 4.01 ppm for 1, 2, and 3, respectively) compared to those of CH 3 (Table 2). These values compare well with those found in the 13 C NMR spectra of C 70 -CHCl 2 + (198 ppm, in CF 3 SO 3 H) [6b] and in the protonated form of C 60 (182 ppm, 1,2-C 6 H 4 Cl 2 ). [12] The slight high-field shifts of the C3 resonances of the chlorinated cations 2-4 compared to that of 1 can most probably be attributed to the interaction of unshared electron pairs at the Cl atoms of the R groups with the cationic C3 center.…”
supporting
confidence: 79%
“…[5] The authors ingeniously identified species formed in solution and assigned their molecular structures based on 1 H NMR studies of the reaction mixtures. Despite the initial progress, further elaboration proved to be unsuccessful (including recording 13 C NMR data), and the preparation and structural characterization of bulk solid products have not been reported to date. The latter task can be very challenging because of the extreme reactivity of the resulting cationic species.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…[28] It is noteworthy that the helical chirality is also important for implementing photon-linked matter qubits in quantum information processing. [15] Our ongoing studies on the (oligo)imidazole-based helicates; preparation of magnetically diluted chiral crystals for synthetic electron-spin qubits, synthesis of novel helicates composed of longer (oligo)imidazoles, f-block helicates, and heteromultimetallic helicates, and functionalization by the introduction of redox-active substituents and electronic-spin-delocalized neutral radical systems, [29] are in progress.…”
Section: Discussionmentioning
confidence: 99%